Analysis of Soil Liquefaction Potential Through Three Field Tests-Based Methods: A Case Study of Babol City - Hasanzadeh, Ali; Rezaei, Sadegh; Shooshpasha, Issa; Ebrahimian Ghajary , Yasser (International Journal of Integrated Engineering, 2021)
During earthquakes, ground failure is commonly caused by liquefaction. Thus, assessment of soil liquefaction potential in earthquake-prone regions is a crucial step towards reducing earthquake hazard. Since Babol city in Iran country is located in a high seismic area, estimation of soil liquefaction potential is of great importance in this city. For this purpose, in the present research, using field-based methods and geotechnical data of 60 available boreholes in Babol, three liquefaction microzonation maps were provided. Finally, one comprehensive liquefaction microzonation map was presented for soil of Babol city. The obtained results in this paper are well in line with the previous investigations. The results indicate that application of different field tests in evaluation of liquefaction is necessary.